Method for surface treatment and / or production of a medical product and medical product
Through multi-step surface treatment methods, including matte, electropolishing, electrochemical etching and re-electropolishing, the problems of material overlap, increased inherent stress and improved reflective characteristics in the surface treatment of existing medical products are solved, and higher corrosion resistance and scratch resistance are achieved.
Patent Information
- Application Number
- CN202411989209.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-06
- Filing Date
- 2021-04-01
- Publication Date
- 2025-04-04
AI Technical Summary
Existing surface treatment methods for medical products are prone to overlapping materials, increasing inherent stress and improving reflective characteristics, affecting the product's corrosion resistance and scratch resistance.
Using a multi-step surface treatment method including matte, electropolishing, electrochemical etching and re-electropolishing, electropolishing and electrochemical etching is performed using an aqueous acid electrolyte solution to form a passivation layer to improve corrosion resistance.
It effectively avoids material overlap and inherent stress increase, reduces the reflective characteristics of the product, and significantly improves the corrosion resistance and scratch resistance of the product.
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application number 202180040714.3 (PCT / EP2021 / 058713) and application date April 1, 2021. Technical Field
[0002] The invention relates to a method for surface treatment or processing and / or manufacturing of a medical product and the medical product. Background Art
[0003] Medical products, such as, in particular, surgical instruments, are often surface treated before they are finished. For this purpose, the surface of the product can be processed, for example, by slide grinding and / or belt grinding. This can eliminate defects in the raw material and / or defects associated with forging, such as decarburized areas, or surface defects such as pores, scars or cracks, which would otherwise have a negative impact on the corrosion resistance of the product.
[0004] However, belt grinding produces fine indentations or protrusions on the product surface. These can be turned over or flattened in subsequent processing steps. This can result in material overlaps. In addition, individual material transfers can occur, for example from silicon oxide particles from the grinding belt to the product surface. This material transfer and the stresses on the medical product associated with the machining can in turn produce or increase inherent stresses in the product. Another problem is that surface defects in the product that were not eliminated or were already produced during grinding can only be eliminated to a limited extent in subsequent processing steps.
[0005] In order to frost the medical product, spherical shot blasting agents, such as glass beads, can be used. This causes plastic deformation of the product surface, thereby increasing and roughening it. Since glass beads are usually very hard (Mohs hardness is 6) and also very brittle, over time, the shot blasting agent will be broken to a certain extent. As a result, both spherical glass beads and broken glass beads will hit the product surface in the frosting step. Broken glass beads produce sharp notches on the product surface, while unbroken glass beads leave spherical indentations on the product surface. Through the impact of broken and unbroken glass beads, there is an interaction between the product surface concave by the broken glass beads and the product surface flattened by the unbroken glass beads. This also leads to material overlap. In addition to plastic deformation and related inherent stress generation, shot blasting may also cause material transfer to the product surface. This material transfer is particularly evident in the notch area, where material accumulation of glass beads may be left.
[0006] As an alternative to the shot blasting treatment using glass beads as an example, the surface of the medical product can be brushed. For this purpose, the product surface can be treated with a brush disk, for example with the aid of a disc-shaped abrasive cloth or a disc-shaped arrangement of nylon fibers with abrasive particles. Aluminum oxide and / or silicon oxide particles are usually applied to the brush disk. Although the corrosion resistance of the product surface is increased by the brushing step compared to the frosted product surface, the disadvantage is that the brushed product surface has more obvious reflective properties than the frosted product surface.
[0007] It is also known that microstructures or indentations formed on the surface of the product by material overlap and the associated generation or increase of inherent stresses in the product have an adverse effect on its corrosion resistance. In the case of material transfer, for example during belt grinding and / or sanding, it also occurs that the transferred material generates additional microstructures and can lead to a weakening of the passivation layer. Summary of the invention
[0008] The object of the present invention is to provide a method for surface treatment or processing and / or manufacturing of medical products, which at least partially avoids the disadvantages occurring in general types of methods, in particular to produce medical products with improved corrosion and scratch resistance and reduced reflection properties.
[0009] Another object of the present invention is to provide corresponding medical products.
[0010] According to the present invention, the above-mentioned object is achieved by a method having the characteristics of the following technical solution 1 and a medical product described in the following technical solution 14. The preferred embodiments of the method and the medical product are the dependent solutions of technical solutions 1 and 14 and the subject of the specification. The technical solution of the present invention includes:
[0011] 1. A method for surface treatment and / or manufacturing of a medical product, wherein the medical product comprises or consists of a metal or an alloy, characterised in that the method comprises the following steps:
[0012] a) Frosting the surface of medical products,
[0013] b) Electropolishing of frosted surfaces of medical products,
[0014] c) electrochemically etching the ground and electropolished surface of the medical product, and
[0015] d) electropolishing the frosted, electropolished and electrochemically etched surface of the medical product,
[0016] wherein step b) and step d) are each carried out at a voltage of 2.0 V to 10.0 V and / or at a current density of 5 A / dm2 to 50 A / dm2, and step c) is carried out at a voltage of 1.2 V to 1.8 V and / or at a current density of 1.4 A / dm2 to 2.4 A / dm2.
[0017] 2. The method according to item 1 above is characterized in that before step a), grinding is performed on the surface of the medical product, preferably sliding grinding and / or belt grinding.
[0018] 3. The method according to 1 or 2 above is characterized in that, in order to perform step a), the surface of the medical product is treated with a peening agent, in particular a ductile and / or cornerless and / or edgeless peening agent, and the peening agent in particular contains or consists of a metal or an alloy.
[0019] 4. The method according to any of the preceding claims, characterized in that step b) is performed for a period of 30 seconds to 130 seconds, in particular 60 seconds to 100 seconds, preferably 90 seconds.
[0020] 5. The method according to any of the preceding items, characterized in that step b) and step d) are each carried out at a voltage of 5 V to 9 V, more preferably 7 V to 8 V and / or each at a current density of 8 A / dm2 to 40 A / dm2, preferably 15 A / dm2 to 20 A / dm2.
[0021] 6. The method according to any of the preceding claims, characterized in that step c) is performed for a period of 30 seconds to 130 seconds, in particular 70 seconds to 110 seconds, preferably 100 seconds.
[0022] 7. The method according to the above is characterized in that step c) is carried out when the voltage applied to the anode is 1.4V to 1.7V, more preferably 1.45V to 1.65V, and / or the current density is 1.6A / dm2 to 2.2A / dm2, preferably 1.8A / dm2 to 2.0A / dm2.
[0023] 8. The method according to any of the preceding claims, characterized in that step d) is carried out for a shorter time than step b), preferably for 5 to 20 seconds, in particular for 7 to 15 seconds, preferably for 10 seconds.
[0024] 9. The method according to any of the preceding claims, characterized in that, for carrying out steps b), c) and d), an acidic aqueous electrolyte solution is used in each case, the acidic aqueous electrolyte solution especially containing an inorganic acid, the inorganic acid especially being selected from phosphoric acid, sulfuric acid and mixtures thereof.
[0025] 10. The method according to any of the preceding claims, characterized in that step e) is performed after step d), i.e. treating the ground, electropolished, electrochemically etched and electropolished again surface of the medical product with a passivating acid or a solution containing a passivating acid.
[0026] 11. The method according to item 10 above is characterized in that the passivating acid used is citric acid and / or nitric acid.
[0027] 12. The method according to any of the preceding items is characterized in that step f) is performed after step e), i.e., the medical product is packaged, and step ef) is performed between step e) and step f), i.e., the medical product is sterilized, or step g) is performed after step f), i.e., the medical product is sterilized.
[0028] 13. The method according to any of the preceding claims, characterized in that the medical product is composed of stainless steel, in particular chromium-containing stainless steel, preferably chromium-containing corrosion-resistant stainless steel, in particular martensitic corrosion-resistant stainless steel.
[0029] 14. A medical product comprising or consisting of a metal or alloy, which is manufactured or manufacturable by any of the methods described above and comprises
[0030] - A passivation layer having a thickness of 1 nm to 10 nm, which at least partially coats the surface of the medical product.
[0031] 15. The medical product according to 14 above is characterized in that the medical product is a medical instrument, especially a surgical instrument.
[0032] In a first aspect, the present invention relates to a method for surface treatment or processing and / or manufacturing of a medical product, wherein the medical product comprises or consists of a metal or an alloy. The method comprises the following steps:
[0033] a) Frosting the surface of medical products,
[0034] b) Electropolishing of frosted surfaces of medical products,
[0035] c) electrochemically etching the ground and electropolished surface of the medical product, and
[0036] d) electropolishing the ground, electropolished and electrochemically etched surface of the medical product.
[0037] The method can comprise the above-mentioned steps, in particular in direct succession.
[0038] The expression "medical product" in the context of the present invention may refer to a medical end product, preferably a surgical instrument, or a precursor, in particular a semi-finished product, a blank or a semi-finished product, or a component of a medical end product, preferably a surgical instrument.
[0039] The expression "alloy" in the context of the present invention is understood to mean a macroscopically homogeneous metallic material consisting of at least two elements (components), at least one of which is a metal. Thus, the expression "alloy" in the context of the present invention may mean a macroscopically homogeneous metallic material consisting of at least two different metals. Alternatively, the expression "alloy" in the context of the present invention may mean a macroscopically homogeneous metallic material consisting of at least one metal and at least one non-metal, such as carbon.
[0040] Surprisingly, it was found that the disadvantages mentioned at the outset with regard to conventional surface treatments of medical products can be partially or even completely avoided by a combination of a sanding step, a (first) electropolishing step, an electrochemical etching step and a further (second) electropolishing step.
[0041] For example, a microstructure that reduces light reflection is produced on the surface of the medical product by a frosting step. The subsequent electropolishing step smoothes this microstructure, thereby producing a smooth and shiny product surface. In addition, the electropolishing step advantageously leads to the formation of a passivation layer, especially a thick and dense passivation layer, on the surface of the electropolished product by adsorbing oxygen, and thus improves the corrosion resistance of the medical product. The subsequent electrochemical etching step is particularly advantageous to also bring about an improvement in the corrosion resistance of the medical product, especially an additional improvement in corrosion resistance. The (additional) improvement in corrosion resistance is particularly (also) attributed to the advantageous formation of a passivation layer on the product surface. In addition, the improvement in corrosion resistance brought about by the electrochemical etching step may be a result of the reduction of material defects that trigger corrosion on the surface of the medical product and / or the avoidance or reduction of compressive and tensile stresses and / or material overlap and / or material superposition. By forming a preferably open microstructure on the product surface, the electrochemical etching step also leads to a (new) reduction in light reflection, which is slightly increased by the (first) electropolishing step due to the smoothing of the microstructure produced by frosting. Therefore, the electrochemical etching step not only improves the corrosion resistance of the medical product, but also leads to the frosting of its surface. This significantly simplifies the handling of the medical product by the user. For example, this can prevent a surgeon in an operating room from being dazzled by the medical product. A subsequent further (second) electropolishing step preferably slightly smoothes the surface of the medical product, thereby obtaining a frosted sheen. As a result, improved reflective properties of the medical product can be achieved, in particular without smoothing the microstructures produced by the electrochemical etching step.
[0042] In the case of medical products made of stainless steel containing chromium or chromium alloys, the positive effect of the electrochemical etching step on the light reflection characteristics and corrosion resistance of the medical product is particularly attributed to the entry of hexavalent chromium ions into the solution during the electrochemical etching operation. As a result, the chromium-rich oxide layer on the surface of the medical product is removed, which enables the acid used for the electrochemical etching operation to directly attack the chemical and physical inhomogeneities of the surface of the medical product, such as the chromium carbide-containing areas around the chromium carbide. This produces a microstructure on the surface of the medical product, especially at the location of the previous chromium carbide area, which is particularly in the form of an etching pit that is preferably open. In addition, the boundary areas, especially the lath and sub-block boundaries, can be advantageously cracked, which can especially cause individual martensitic laths to extend. The result is a roughened and particularly frosted product surface on which incident light can be scattered. The risk of nucleation sites for pitting corrosion is also advantageously reduced by reducing the chromium-poor areas on the surface of the medical product.
[0043] Further advantages of the method relate to the improved cleanability of the medical product and, in particular, the lower tendency for the surface of the medical product to discolor. DETAILED DESCRIPTION
[0044] In one embodiment of the invention, grinding, preferably slide grinding and / or belt grinding, is performed on the surface of the medical product before step a) is performed.
[0045] For sliding grinding, the medical product is preferably introduced into a container together with the sliding grinding body, which is preferably in the form of a bulk material, or with an aqueous solution containing the sliding grinding body and optional additives. The optional additives can be selected from corrosion inhibitors, degreasing agents, pickling agents, separating agents (e.g. plastic balls with a diameter of <1 mm) and mixtures thereof. By means of such a solution, the abrasive material generated by the sliding grinding body and the product stripping material can be advantageously absorbed and transported away. Depending on the additives used in each case, other effects such as corrosion protection, degreasing and adhesion prevention can also be achieved.
[0046] The oscillating or rotating movement of the container generates a relative movement between the medical product and the sliding abrasive body. This results in material removal from the medical product, especially at its edges. The surface image, roughness, material removal and deburring properties of the medical product can be advantageously influenced in a targeted manner by the machine used for sliding abrasion, the abrasive body and any additives.
[0047] The sliding abrasive body may comprise or consist of a material selected from the group consisting of ceramics, plastics, natural products such as walnut shells, steel and combinations thereof.
[0048] In principle, the sliding grinding bodies can have regular and / or irregular shapes.
[0049] In particular, the sliding grinding body can be non-corner and / or non-edge-shaped, for example, oval, annular or spherical.
[0050] Alternatively or in combination, the sliding grinding body can have corners and / or edges. In particular, the sliding grinding body can be polyhedral, such as a cube, a cuboid, a prism, a pyramid or a spar. In addition, the sliding grinding body can be a straight prism and / or an oblique prism.
[0051] Alternatively or in combination, the sliding grinding body can be conical and / or truncated-conical.
[0052] In addition, a mixture of sliding abrasive bodies of different shapes can be used for sliding abrasion of medical products. For example, sliding abrasive bodies without corners and / or edges and polyhedral sliding abrasive bodies can be used. Alternatively or in combination, sliding abrasive bodies without corners and / or edges of different shapes and / or different polyhedral sliding abrasive bodies can be used. With regard to the conceivable configurations and shapes, reference is made entirely to the configurations and shapes for the sliding abrasive bodies described in the previous paragraphs.
[0053] The sliding grinding body can also have at least one size, especially at least one average size, such as diameter, especially average diameter, and / or height, especially average height, and / or length, especially average length, which is 1mm to 80mm. In the context of the present invention, the diameter of the spherical sliding grinding body should be understood to refer to twice the radius of a single spherical sliding grinding body. On the contrary, in the context of the present invention, the diameter of the non-spherical sliding grinding body should be understood to refer to the maximum possible distance between two points, and these two points can be taken relative to each other along the circumference of the single non-spherical sliding grinding body. The average size mentioned in this paragraph can be determined, for example, by bulk density and / or optical measurement. Sliding grinding can also be carried out in the form of roller sliding grinding, vibration sliding grinding, immersed sliding cutting, drag grinding, centrifugal sliding cutting or pressure flow grinding.
[0054] For belt grinding of medical products, preferably grinding belts are used. For this purpose, grinding belts running on at least two rollers can be used in particular. The grinding belt preferably has a particle size of 150 to 1200. The number of particle sizes depends on the measurement unit mesh, i.e. the number of meshes per inch (25.4 mm) of the net. Thus, for example, a grinding medium with a particle size of 150 will just pass through a sieve with 150 meshes per inch.
[0055] According to the invention, before step a), for example, sliding grinding can first be carried out and then belt grinding can be carried out. Belt grinding can be advantageous in particular for the treatment of so-called shadow areas of the medical product, but also outside such areas. The shadow area defines an area of the medical product in which the sliding grinding bodies are ineffective or have only a limited effect on the surface, in particular due to the geometry and / or construction of the medical product.
[0056] Alternatively, before step a), the surface of the medical product can be ground only by sliding grinding. This can avoid the formation of notches and / or protrusions on the product surface caused by belt grinding, thus additionally improving the corrosion resistance of the medical product.
[0057] Alternatively, the surface of the medical product may be ground only by belt grinding before carrying out step a).
[0058] In another embodiment of the invention, during or in order to carry out step a), the surface of the medical product is treated with a peening agent, in particular a ductile, i.e. non-brittle, peening agent. The use of ductile peening agents has the advantage, in particular, that the formation of notches and / or microstructures, in particular in the form of micro-crevices, can be prevented or at least reduced. This in turn can avoid or at least reduce the occurrence of local stress peaks in the medical product, in particular additionally improving the corrosion resistance of the medical product. In addition, by using such peening agents, the scratch resistance of the medical product can be advantageously (additionally) improved.
[0059] In principle, the blasting agent can comprise or consist of a material which is selected from the group consisting of metals, metal oxides, alloys, ceramics, plastics, vegetable material, sand and combinations thereof.
[0060] The metal oxide may in particular be corundum (Al 2 O 3 ).
[0061] The plastic may be, in particular, a urea resin, a phenolic resin, a polyester resin or a melamine resin.
[0062] The ceramic may in particular be a glass or a hybrid ceramic.
[0063] The alloy may be a steel, in particular a stainless steel. The alloy is preferably a stainless steel, in particular a stainless steel. For suitable stainless steels, reference is made to the following description.
[0064] The sand may in particular be garnet sand.
[0065] The shot peening agent preferably comprises a metal or an alloy, or the shot peening agent preferably consists of a metal or an alloy. Regarding suitable metals and alloys, reference is made to the description above. This shot peening agent has the particular advantage that it does not break and therefore does not cause notches on the surface of the medical product. In addition, material transfer to the product surface can be reduced or even completely avoided. Overall, this can additionally improve the corrosion resistance of the medical product and avoid undesirable inherent stresses in the product. In addition, this shot peening agent is particularly suitable for improving the scratch resistance of the medical product.
[0066] Particularly preferably, the shot blasting agent comprises steel, in particular stainless steel, or the shot blasting agent preferably consists of steel, in particular stainless steel. Through this shot blasting agent, the advantages mentioned in the previous paragraph can be particularly clearly demonstrated.
[0067] In principle, the shot can have a regular and / or irregular shape, in particular in the form of a regularly and / or irregularly shaped shot body.
[0068] It is also particularly preferred that the shot is cornerless and / or edgeless, in particular in the form of a cornerless and / or edgeless shot body. This can avoid the formation of indentations on the surface of the medical product, thereby additionally improving its corrosion resistance.
[0069] In principle, the blasting shots can be in the form of ellipsoidal, annular, spherical or beaded shapes or in the form of correspondingly shaped blasting shot bodies.
[0070] The shot is preferably spherical and / or beaded, or in the form of spherical and / or beaded shot bodies.
[0071] Alternatively or in combination, the shot may have corners and / or edges. In particular, the shot may be a polyhedron, such as a cube, a cuboid, a prism, a pyramid or a spar, or in the form of a shot body of a corresponding shape. The shot may also have the shape of a right prism or an oblique prism, or in the form of a shot body of a corresponding shape.
[0072] Alternatively or in combination, the shot may be conical and / or frustoconical, or be in the form of a conical and / or frustoconical shot body.
[0073] Alternatively or in combination, the shot can be in spherical form, for example in the form of round wires, or in the form of correspondingly shaped shot bodies. Particularly preferably, the shot can be in the form of stainless steel wire particles.
[0074] Alternatively or in combination, the shot may be in fragmented form, in particular in the form of fragmented shot bodies.
[0075] Furthermore, the shot or shot body may have at least one dimension, in particular at least one average dimension, such as a diameter, in particular an average diameter, and / or a height, in particular an average height, and / or a length, in particular an average length, which is between 40 μm and 2000 μm. In the context of the present invention, the diameter of a spherical shot or a spherical shot body is to be understood here as twice the radius of the spherical shot or of an individual spherical shot body. In contrast, in the context of the present invention, the diameter of a non-spherical shot or a non-spherical shot body is to be understood as meaning the maximum possible distance between two points which can be taken relative to one another along the circumference of the non-spherical shot or of an individual non-spherical shot. The average dimensions mentioned in this paragraph can be determined, for example, by laser diffraction or sieve analysis.
[0076] In order to accelerate the peening agent or the peening agent body onto the surface of the medical product, for example, a pressure jet device, an ejector jet device or an impeller device can be used. If a pressure jet device or an ejector jet device is used, a pressure of 1 bar to 6 bar can be used.
[0077] Typically, the surface of the medical product is anodically stripped in an electrolyte solution during or for the purpose of performing step b), ie the medical product typically forms an anode in an electrochemical cell during or for the purpose of performing step b).
[0078] In another embodiment of the present invention, step b) is performed for a period of 30 seconds to 130 seconds, in particular 60 seconds to 100 seconds, preferably 90 seconds.
[0079] In principle, steps b) and d) can be carried out at different voltages, in particular at a DC voltage. Steps b) and d) are preferably each carried out at the same voltage, in particular at a DC voltage.
[0080] In another embodiment of the present invention, step b) and / or step d), in particular step b) and step d), are each carried out at a voltage of ≥ 2.0 V, in particular 2.0 V to 10.0 V, preferably 5 V to 9 V, more preferably 7 V to 8 V, in particular a DC voltage. In particular, by the voltage values disclosed in this paragraph, the formation of a uniform polishing film and a uniform transfer of the metal or alloy to the electrolyte solution can be achieved.
[0081] Furthermore, step b) and / or step d) can be performed at / with a constant or varying voltage, in particular a DC voltage. Regarding suitable voltage ranges / values, reference is made to the voltages disclosed in the previous paragraphs.
[0082] In another embodiment of the present invention, step b) and / or step d), in particular step b) and step d), are each at / at 5 A / dm 2 Up to 50A / dm 2 , especially 8A / dm2 Up to 40A / dm 2 , preferably 15A / dm 2 Up to 20A / dm 2 The current density is carried out.
[0083] Furthermore, step b) and / or step d) can be carried out several times, in particular two, three or four times. In particular, steps b) and d) can be repeated a different number of times. By repeating steps b) and d) several times, it is particularly advantageous to uniformly process geometrical properties of the medical product, such as the sealing of the medical product, without the formation of associated shadows. For example, the sealing of the medical product can be processed at two locations so that only a small amount of shadows is formed. Alternatively, it may be preferred to slowly manufacture the medical product when carrying out steps b) and / or d).
[0084] Alternatively, step b) and / or step d) may be performed only once.
[0085] Furthermore, the medical product may be cleaned and / or degreased before carrying out step b) and / or before carrying out step d).
[0086] Typically, the surface of the medical product is (likewise) anodically stripped in an electrolyte solution during or for step c), ie the medical product typically forms an anode in an electrochemical cell during or for step c).
[0087] In another embodiment of the invention, step c) is carried out for 30 seconds to 130 seconds, in particular 60 seconds to 100 seconds or 70 seconds to 110 seconds, preferably 90 seconds or 100 seconds. In principle, step c) can be carried out for a shorter or longer time than step b). Preferably, steps b) and d) are carried out for the same length of time.
[0088] In another embodiment of the present invention, step c) is carried out at / with a voltage preferably measured at the anode (at the medical product to be surface treated or processed and / or manufactured) of ≤2.1V, especially <2V, especially 1.2V to 1.8V, preferably 1.4V to 1.7V, more preferably 1.4V to 1.5V or 1.45V to 1.65V, especially a DC voltage. In this embodiment of the present invention, the advantages according to the present invention that can be achieved by the electrochemical etching step are particularly significantly produced. Preferably, the voltage is measured at the anode (at the medical product to be surface treated or processed and / or manufactured) by a silver-silver chloride electrode. The determined voltage is then converted to a standard hydrogen electrode. Typically, the voltage is set at the current source without knowing which part of the voltage is applied to the anode and how much is applied to the remaining resistance (e.g., wire, electrolyte, etc.). In the present invention, the accurate voltage at the anode is preferably crucial.
[0089] Furthermore, step c) can be performed at / with a constant or varying voltage, in particular a DC voltage. Regarding suitable voltage ranges / values, reference is made to the voltages disclosed in the previous paragraphs.
[0090] In another embodiment of the present invention, step c) is carried out at 1.4 A / dm 2 Up to 2.4A / dm 2 , especially 1.6A / dm 2 Up to 2.2A / dm 2 , preferably 1.8A / dm 2 Up to 2.0A / dm 2 The (low) current densities disclosed in this paragraph allow particularly good control of the electrochemical etching of the surface of the medical product over time.
[0091] Furthermore, step c) may be performed at a temperature of 20°C to 90°C, in particular 50°C to 80°C, preferably 70°C to 80°C.
[0092] Preferably step c) is carried out a plurality of times, in particular two, three or four times.
[0093] By repeating step c) several times, geometrical properties of the medical product, such as the sealing of the medical product, can (also) be processed uniformly, particularly advantageously, without causing associated shadows. For this purpose, the sealing of the medical product can (also) be processed, for example, at two locations, so that only a few shadows are formed. Alternatively, it may be preferred to (also) slowly produce the medical product when carrying out step c).
[0094] Alternatively, step c) may be performed only once.
[0095] Typically, the surface of the medical product is (also) anodically stripped in an electrolyte solution during or for the purpose of performing step d), i.e. the medical product typically forms an anode in an electrochemical cell during or for the purpose of performing step d).
[0096] In another embodiment of the present invention, step d) is performed for a shorter time than step b). Preferably, step d) is performed for a time of 5 to 20 seconds, especially 7 to 15 seconds, preferably 10 seconds.
[0097] In another embodiment of the invention, for carrying out steps b), c) and d), an acidic aqueous electrolyte solution is used in each case, which in particular comprises an inorganic acid or an inorganic acid mixture. The inorganic acid is preferably selected from phosphoric acid, sulfuric acid and mixtures thereof. It has been found that phosphoric acid- and / or sulfuric acid-containing aqueous electrolyte solutions are particularly advantageous for treating the surface of medical products made of stainless steel, in particular rust-proof or corrosion-resistant stainless steel.
[0098] The inorganic acid content of the acidic aqueous electrolyte solution may be 50% to 95% by weight, in particular 60% to 95% by weight, preferably 75% to 95% by weight, based on the total weight of the acidic aqueous electrolyte solution. In particular, the phosphoric acid content of the acidic aqueous electrolyte solution may be 20% to 70% by weight, in particular 30% to 60% by weight, preferably 40% to 50% by weight, and / or the sulfuric acid content may be 10% to 70% by weight, in particular 20% to 60% by weight, preferably 30% to 50% by weight, each based on the total weight of the acidic aqueous electrolyte solution.
[0099] The acidic aqueous electrolyte solution may also be an aged acidic aqueous electrolyte solution.
[0100] The acidic aqueous electrolyte solution may also contain additives such as surfactants.
[0101] It is also advantageous that the aggressiveness of the acidic aqueous electrolyte solution can be controlled in a targeted manner via its water content. For example, the water content of the acidic aqueous electrolyte solution can be 5% to 25% by weight, in particular 5% to 15% by weight, preferably 5% to 10% by weight, based on the total weight of the acidic aqueous electrolyte solution.
[0102] In principle, steps b), c) and d) can each be carried out with a different acidic electrolyte aqueous solution, which in particular comprises an inorganic acid or an inorganic acid mixture. Alternatively, steps b) and d) can each be carried out with the same acidic electrolyte aqueous solution, which in particular comprises an inorganic acid or an inorganic acid mixture. In particular, the acidic electrolyte aqueous solution (which in particular comprises an inorganic acid or an inorganic acid mixture) used to carry out steps b) and d) can be different from the acidic electrolyte aqueous solution (which in particular comprises an inorganic acid or an inorganic acid mixture) used to carry out step c), in particular in terms of the inorganic acid and / or the inorganic acid content. With regard to suitable inorganic acids and inorganic acid contents, reference is made to the above statements in their entirety.
[0103] In another embodiment of the present invention, step e) is performed after step d), i.e. the sanded, electropolished, electrochemically etched and electropolished again surface of the medical product is treated with a passivating acid or a solution containing a passivating acid. In other words, in another embodiment of the present invention, step e) is performed after step d), i.e. the sanded, electropolished, electrochemically etched and electropolished again surface of the medical product is passivated. In this way, it is particularly advantageous to additionally enhance or promote the formation of a passivation layer on the surface of the medical product and thus additionally improve the corrosion resistance of the medical product. In the case of medical products made of stainless steel containing chromium or a chromium alloy, for example, an enhanced chromium oxide layer can be formed on the surface of the medical product by the passivation step.
[0104] In another embodiment of the present invention, the passivating acid used is citric acid, nitric acid or a mixture thereof.
[0105] The solution containing the passivating acid used for carrying out step e) is preferably an aqueous solution containing citric acid, in particular having a citric acid content of 5% to 60% by weight, based on the total weight of the aqueous solution containing citric acid. Alternatively, the solution containing the passivating acid used for carrying out step e) is preferably an aqueous solution containing nitric acid, in particular having a nitric acid content of 5% to 60% by weight, based on the total weight of the aqueous solution containing nitric acid.
[0106] The use of citric acid is superior to the use of nitric acid both from a health point of view and from an operational safety point of view. In addition, with citric acid, thicker chromium oxide layers can be achieved for medical products made of stainless steel containing chromium or chromium alloys than with nitric acid, since in the case of such stainless steels, nitric acid also reduces the content of other alloying components.
[0107] To carry out step e), the medical product can be immersed in, for example, a passivating acid or a solution containing the passivating acid. Alternatively, the passivating acid or a solution containing the passivating acid can be sprayed or poured on the surface of the medical product.
[0108] Furthermore, step e) may be performed for a period of 2 minutes to 2 hours, in particular 5 minutes to 60 minutes, preferably 10 minutes to 30 minutes.
[0109] Furthermore, step e) may be performed at a temperature ranging from 20°C to 80°C, especially from 30°C to 65°C, preferably from 50°C to 60°C.
[0110] Furthermore, between step d) and step e), step d) may be performed, namely cleaning and / or degreasing the medical product, in particular cleaning and / or degreasing the sanded, electropolished, electrochemically etched and electropolished again surface of the medical product.
[0111] In another embodiment of the present invention, step f) is performed after step e), i.e. the medical product is packaged and / or marked, in particular labeled. Preferably, step ef) is performed between step e) and step f), i.e. the medical product is sterilized, in particular steam sterilized. Alternatively, it may be preferred to perform step g), i.e. the medical product is sterilized, in particular steam sterilized, after step f).
[0112] In another embodiment of the invention, the medical product comprises or consists of steel, preferably stainless steel.
[0113] The expression "stainless steel" (according to EN 10020) in the context of the present invention is understood to mean alloyed or unalloyed steels having a certain purity level, for example having a sulfur and / or phosphorus mass content of ≤0.025%, in particular <0.025%.
[0114] In particular, the stainless steel may contain at least one alloying element selected from the group consisting of chromium, nickel, molybdenum, titanium, niobium, tungsten, vanadium, cobalt and combinations thereof.
[0115] In particular, the stainless steel may have a chromium content of 10% to 25% by mass.
[0116] Further preferably, the stainless steel is rust-free or corrosion-resistant stainless steel.
[0117] Further preferably, the stainless steel is a stainless steel containing chromium or a chromium alloy. Preferably, the stainless steel is a chromium-containing corrosion-resistant stainless steel or a chromium alloy corrosion-resistant stainless steel.
[0118] Furthermore, the stainless steel may in particular be a martensitic, ferritic or austenitic stainless steel.
[0119] Preferably, the stainless steel is a martensitic corrosion resistant stainless steel, in particular a so-called carbon martensitic, ie a corrosion resistant stainless steel with chromium and carbon as main alloying components, or a so-called nickel martensitic, ie a corrosion resistant stainless steel with nickel as main alloying component, according to ISO 7153-1.
[0120] In particular, the stainless steel may be a martensitic stainless steel having a chromium content of 10.5 to 13% by mass and / or a carbon content of 0.2 to 1% by mass.
[0121] Alternatively, the stainless steel may in particular be an austenitic stainless steel having a chromium content of 16 to 21% by mass and / or a carbon content of 0.02 to 0.12% by mass.
[0122] Alternatively, the stainless steel may in particular be a ferritic stainless steel having a chromium content of 12% to 18% by mass and / or a carbon content of <0.2% by mass.
[0123] For example, the stainless steel may be a stainless steel with the material abbreviation X12Cr13 (material number 1.4006), which is a martensitic stainless steel with a carbon content of 0.08% to 0.15%, a chromium content of 11.5% to 13.5%, and a nickel content of ≤0.75%.
[0124] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X12CrS13 (material number 1.4005), wherein the carbon content of the stainless steel is 0.08% to 0.15%, the chromium content is 12.0% to 14.0%, the molybdenum content is ≤ 0.60%, and the optional sulfur content is 0.15% to 0.35%.
[0125] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X20Cr13 (material number: 1.4021), wherein the carbon content of the stainless steel is 0.16% to 0.25% by mass and the chromium content is 12.0% to 14.0% by mass.
[0126] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X15Cr13 (material number: 1.4024), wherein the carbon content of the stainless steel is 0.12% to 0.17% and the chromium content of the stainless steel is 12.0% to 14.0%.
[0127] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X30Cr13 (material number: 1.4028), wherein the carbon content of the stainless steel is 0.26% to 0.35% by mass and the chromium content is 12.0% to 14.0% by mass.
[0128] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X46Cr13 (material number: 1.4034), wherein the carbon content of the stainless steel is 0.43% to 0.50% by mass and the chromium content is 12.5% to 14.5% by mass.
[0129] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X50CrMoV15 (material number: 1.4116), wherein the carbon content of the stainless steel is 0.45% to 0.55%, the chromium content is 14.0% to 15.0%, the molybdenum content is 0.50% to 0.80%, and the vanadium content is 0.10% to 0.20%.
[0130] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X17CrNi16-2 (material number: 1.4057), wherein the carbon content of the stainless steel is 0.12% to 0.22%, the chromium content is 15.0% to 17.0%, and the nickel content is 1.5% to 2.5%.
[0131] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X39CrMo17-1 (material number: 1.4122), wherein the carbon content of the stainless steel is 0.33% to 0.45%, the chromium content is 15.5% to 17.5%, the molybdenum content is 0.8% to 1.3%, and the nickel content is ≤1.0%.
[0132] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X14CrMoS17 (material number: 1.4104), wherein the carbon content of the stainless steel is 0.10% to 0.17%, the chromium content is 15.5% to 17.5%, the molybdenum content is 0.20% to 0.60%, and the sulfur content is 0.15% to 0.35%.
[0133] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X3CrNiMo13-4 (material number: 1.4313), wherein the carbon content of the stainless steel is ≤ 0.05%, the chromium content is 12.0% to 14.0%, the molybdenum content is 0.3% to 0.7%, and the nickel content is 3.5% to 4.5%.
[0134] Alternatively, the stainless steel may be a martensitic corrosion-resistant stainless steel with the material abbreviation X4CrNiMo16-5-1 (material number: 1.4418), wherein the carbon content of the stainless steel is ≤0.06%, the chromium content is 15.0% to 17.0%, the molybdenum content is 0.80% to 1.50%, and the nickel content is 4.0% to 6.0%.
[0135] Alternatively, the stainless steel may be a martensitic stainless steel with the material abbreviation X65Cr13, wherein the carbon content of the stainless steel is 0.58% to 0.70%, the chromium content is 12.5% to 14.5%, the manganese content is ≤1.00%, the silicon content is ≤1.00%, the phosphorus content is 0.04%, and the sulfur content is 0.015%.
[0136] Alternatively, the stainless steel may be a martensitic stainless steel with the material abbreviation X30CrMoN15-1 (material number: 1.4108), wherein the carbon mass content of the stainless steel is 0.25% to 0.35%, the chromium mass content is 14.0% to 16.0%, the molybdenum mass content is 0.85% to 1.10%, the nickel mass content is 0.50%, the manganese mass content is 1.00%, the silicon mass content is 1.00%, and the nitrogen mass content is 0.03% to 0.50%.
[0137] Alternatively, the stainless steel may be a martensitic stainless steel with the material abbreviation X70CrMo15 (material number: 1.4109), which has a carbon mass content of 0.60% to 0.75%, a chromium mass content of 14.0% to 16.0%, a molybdenum mass content of 0.40% to 0.80%, a manganese mass content of ≤1.00%, a silicon mass content of ≤0.70%, a phosphorus mass content of 0.04% and a sulfur mass content of 0.015%.
[0138] Alternatively, the stainless steel may be a martensitic stainless steel with the material abbreviation X90CrMoV18 (material number: 1.4112), which has a carbon content of 0.90%, a chromium content of 17% to 19%, and a molybdenum content of 0.90%.
[0139] Alternatively, the stainless steel may be a martensitic stainless steel with the material abbreviation X38CrMoV15 (material number: 1.4117), which has a carbon content of 0.38%, a chromium content of 14% to 15%, and a molybdenum content of 0.50%.
[0140] Alternatively, the stainless steel may be a martensitic stainless steel with the material abbreviation X150CrMo17 (material number: 1.4125), which has a carbon content of 1.10%, a chromium content of 17%, and a molybdenum content of 0.60%.
[0141] Alternatively, the stainless steel may be a martensitic stainless steel with the material abbreviation X22CrMoNiS13-1 (material number: 1.4121), wherein the carbon mass content of the stainless steel is 0.20% to 0.25%, the chromium mass content is 12.0% to 14.0%, the molybdenum mass content is 1.00% to 1.50%, the nickel mass content is 0.80% to 1.20%, the manganese mass content is 1.00% to 1.50%, the silicon mass content is ≤1.00%, the phosphorus mass content is 0.045%, and the sulfur mass content is 0.15% to 0.25%.
[0142] Alternatively, the stainless steel may be a martensitic stainless steel with the material abbreviation X40CrMoVN16-2 (material number: 1.4123), wherein the carbon mass content of the stainless steel is 0.35% to 0.50%, the chromium mass content is 14.0% to 16.0%, the molybdenum mass content is 1.00% to 2.50%, the nickel mass content is 0.5%, the manganese mass content is ≤1.00%, the silicon mass content is ≤1.00%, the phosphorus mass content is 0.04%, and the sulfur mass content is 0.015%.
[0143] Alternatively, the stainless steel may be a martensitic stainless steel with the material abbreviation X105CrMo17 (material number: 1.4125), wherein the carbon content of the stainless steel is 0.95% to 1.20%, the chromium content is 16.0% to 18.0%, the molybdenum content is 0.04% to 0.80%, the manganese content is at most 1.00%, the silicon content is at most 1.00%, the phosphorus content is at most 0.040%, and the sulfur content is at most 0.015%.
[0144] Alternatively, the stainless steel may be a precipitation hardened corrosion resistant stainless steel with the material abbreviation X5CrNiCuNb16-4 (material number: 1.4542), wherein the carbon mass content of the stainless steel is ≤0.07%, the chromium mass content is 15.0% to 17.0%, the molybdenum mass content is ≤0.60%, the nickel mass content is 3.0% to 5.0%, the copper mass content is 3.0% to 5.0%, and the niobium mass content is at most 0.45%.
[0145] Alternatively, the stainless steel may be a precipitation hardened corrosion resistant stainless steel with the material abbreviation X7CrNiAl17-7 (material number: 1.4568), wherein the carbon mass content of the stainless steel is ≤ 0.09%, the chromium mass content is 16.0% to 18.0%, the nickel mass content is 6.5% to 7.8%, and the aluminum mass content is 0.70% to 1.50%.
[0146] Alternatively, the stainless steel may be a precipitation hardening corrosion resistant stainless steel with the material abbreviation X5CrNiMoCuNb14-5 (material number: 1.4594), wherein the carbon mass content of the stainless steel is ≤0.07%, the chromium mass content is 13.0% to 15.0%, the molybdenum mass content is 1.20% to 2.00%, the nickel mass content is 5.0% to 6.0%, the copper mass content is 1.20% to 2.00%, and the niobium mass content is 0.15% to 0.60%.
[0147] Alternatively, the stainless steel may be a precipitation hardening corrosion resistant stainless steel with the material abbreviation X3CrNiTiMb12-9 (material number: 1.4543), wherein the carbon mass content of the stainless steel is ≤0.03%, the chromium mass content is 11.0% to 12.5%, the molybdenum mass content is ≤0.50%, the nickel mass content is 3.00% to 5.00%, the titanium mass content is ≤0.90% to 1.40%, the copper mass content is 1.50% to 2.50%, the niobium mass content is 0.10% to 0.50%, the manganese mass content is 0.50%, the silicon mass content is 0.50%, the phosphorus mass content is ≤0.02%, and the sulfur mass content is ≤0.015%.
[0148] Alternatively, the stainless steel may be a ferritic corrosion-resistant stainless steel with the material abbreviation X2CrNi12 (material number: 1.4003), wherein the carbon content of the stainless steel is ≤0.03%, the chromium content is 10.5% to 12.5%, the nickel content is 0.3% to 1.00%, and the nitrogen content is ≤0.03%.
[0149] Alternatively, the stainless steel may be a ferritic corrosion-resistant stainless steel with the material abbreviation X2CrNi12 (material number: 1.4512), wherein the carbon content of the stainless steel is ≤ 0.03%, the chromium content is 10.5% to 12.5%, and the titanium content is at most 0.65%.
[0150] Alternatively, the stainless steel may be a ferrite corrosion-resistant stainless steel with the material abbreviation X6Cr17 (material number: 1.4016), wherein the carbon mass content of the stainless steel is ≤ 0.08% and the chromium mass content is 16.0% to 18.0%.
[0151] Alternatively, the stainless steel may be a ferritic corrosion-resistant stainless steel with the material abbreviation X3CrTi17 (material number: 1.4510), wherein the carbon content of the stainless steel is ≤ 0.05%, the chromium content is 16.0% to 18.0%, and the titanium content is at most 0.80%.
[0152] Alternatively, the stainless steel may be a ferritic corrosion-resistant stainless steel with the material abbreviation X6CrMoS17 (material number: 1.4105), wherein the carbon content of the stainless steel is ≤ 0.08%, the chromium content is 16.0% to 18.0%, the molybdenum content is 0.20% to 0.60%, and the sulfur content is 0.15% to 0.35%.
[0153] Alternatively, the stainless steel may be a ferritic corrosion-resistant stainless steel with the material abbreviation X3CrNb17 (material number: 1.4511), wherein the carbon content of the stainless steel is ≤ 0.05%, the chromium content is 16.0% to 18.0%, and the niobium content is at most 1.00%.
[0154] Alternatively, the stainless steel may be a ferritic corrosion-resistant stainless steel with the material abbreviation X2CrTiNb18 (material number: 1.4509), wherein the carbon content of the stainless steel is ≤0.03%, the chromium content is 17.5% to 18.5%, the niobium content is at most 1.00%, and the titanium content is 0.10% to 0.60%.
[0155] Alternatively, the stainless steel may be a ferritic corrosion-resistant stainless steel with the material abbreviation X6CrMo17-1 (material number: 1.4113), wherein the carbon content of the steel is ≤ 0.08%, the chromium content is 16.0% to 18.0%, and the molybdenum content is 0.90% to 1.40%.
[0156] Alternatively, the stainless steel may be a ferritic corrosion-resistant stainless steel with the material abbreviation X2CrMoTi18-2 (material number: 1.4521), wherein the carbon content of the stainless steel is ≤ 0.025%, the chromium content is 17.0% to 20.0%, the molybdenum content is 1.80% to 2.50%, and the titanium content is at most 0.80%.
[0157] Alternatively, the stainless steel may be an austenitic-ferritic corrosion-resistant stainless steel with the material abbreviation X2CrNi22-2 (material number: 1.4062), wherein the carbon mass content of the stainless steel is ≤0.03%, the chromium mass content is 21.5% to 24.0%, the molybdenum mass content is ≤0.45%, the nickel mass content is 1.00% to 2.90%, and the nitrogen mass content is 0.16% to 0.28%.
[0158] Alternatively, the stainless steel may be an austenitic-ferrite corrosion-resistant stainless steel with the material abbreviation X2CrMnNiN21-5-1 (material number: 1.4162), wherein the carbon mass content of the stainless steel is ≤0.04%, the chromium mass content is 21.0% to 22.0%, the molybdenum mass content is 0.10% to 0.80%, the nickel mass content is 1.35% to 1.70%, the manganese mass content is 4.0% to 6.0%, the nitrogen mass content is 0.20% to 0.25%, and the copper mass content is 0.10% to 0.80%.
[0159] Alternatively, the stainless steel may be an austenitic-ferritic corrosion-resistant stainless steel with the material abbreviation X2CrNiN23-4 (material number: 1.4362), wherein the carbon mass content of the stainless steel is ≤0.03%, the chromium mass content is 22.0% to 24.0%, the molybdenum mass content is 0.10% to 0.60%, the nickel mass content is 3.5% to 5.5%, and the copper mass content is 0.10% to 0.60%.
[0160] Alternatively, the stainless steel may be an austenitic-ferritic corrosion-resistant stainless steel with the material abbreviation X2CrNiMoN22-5-3 (material number: 1.4462), wherein the carbon mass content of the stainless steel is ≤0.03%, the chromium mass content is 21.0% to 23.0%, the molybdenum mass content is 2.5% to 3.5%, the nickel mass content is 4.5% to 6.5%, and the nitrogen mass content is 0.10% to 0.22%.
[0161] Alternatively, the stainless steel may be an austenitic-ferritic corrosion-resistant stainless steel with the material abbreviation X2CrNiMnMoCuN24-4-3-2 (material number: 1.4662), wherein the carbon mass content of the stainless steel is ≤0.03%, the chromium mass content is 23.0% to 25.0%, the molybdenum mass content is 1.00% to 2.00%, the nickel mass content is 3.0% to 4.5%, the manganese mass content is 2.5% to 4.0%, and the copper mass content is 0.10% to 0.80%.
[0162] Alternatively, the stainless steel may be an austenitic-ferritic corrosion-resistant stainless steel with the material abbreviation X2CrNiMoN25-7-4 (material number: 1.4410), wherein the carbon mass content of the stainless steel is ≤0.03%, the chromium mass content is 24.0% to 26.0%, the molybdenum mass content is 3.0% to 4.5%, the nickel mass content is 6.0% to 8.0%, and the nitrogen mass content is 0.24% to 0.35%.
[0163] Alternatively, the stainless steel may be an austenitic-ferrite corrosion-resistant stainless steel with the material abbreviation X2CrNiMoCuWN25-7-4 (material number: 1.4501). The stainless steel has a carbon mass content of ≤0.03%, a chromium mass content of 24.0% to 26.0%, a molybdenum mass content of 3.0% to 4.0%, a nickel mass content of 6.0% to 8.0%, a copper mass content of 0.50% to 1.00%, a tungsten mass content of 0.50% to 1.00%, and a nitrogen mass content of 0.20% to 0.30%.
[0164] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X2CrNiMo18-15-3 (material number: 1.4441), wherein the carbon content of the stainless steel is at most 0.030%, the chromium content is 17.0% to 19.0%, the molybdenum content is 2.7% to 3.0%, the nickel content is 13.0% to 15.0%, the manganese content is at most 2.00%, the copper content is at most 0.50%, the silicon content is at most 0.75%, the phosphorus content is at most 0.025%, the sulfur content is at most 0.003%, and the nitrogen content is at most 0.10%.
[0165] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X5CrNi18-10 (material number: 1.4301), wherein the carbon content of the stainless steel is ≤0.07%, the chromium content is 17.5% to 19.5%, the nickel content is 8.0% to 10.5%, and the nitrogen content is ≤0.11%.
[0166] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X4CrNi18-12 (material number: 1.4303), wherein the carbon content of the stainless steel is ≤0.06%, the chromium content is 17.0% to 19.0%, the nickel content is 11.0% to 13.0%, and the nitrogen content is ≤0.11%.
[0167] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X8CrNiS18-9 (material number: 1.4305), wherein the carbon mass content of the stainless steel is ≤0.10%, the chromium mass content is 17.0% to 19.0%, the nickel mass content is 8.0% to 10.0%, the sulfur mass content is 0.15% to 0.35%, and the copper mass content is ≤1.00%.
[0168] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X2CrNi19-11 (material number: 1.4306), wherein the carbon mass content of the stainless steel is ≤0.030%, the chromium mass content is 18.0% to 20.0%, the nickel mass content is 10.0% to 12.0%, and the nitrogen mass content is ≤0.11%.
[0169] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X2CrNi18-9 (material number: 1.4307), wherein the carbon content of the stainless steel is ≤0.030%, the chromium content is 17.5% to 19.5%, the nickel content is 8.0% to 10.5%, and the nitrogen content is ≤0.11%.
[0170] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X2CrNi18-10 (material number: 1.4311), wherein the carbon content of the stainless steel is ≤ 0.030%, the chromium content is 17.5% to 19.5%, the nickel content is 8.5% to 11.5%, and the nitrogen content is 0.12% to 0.22%.
[0171] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X6CrNiTi18-10 (material number: 1.4541), wherein the carbon content of the stainless steel is ≤ 0.08%, the chromium content is 17.0% to 19.0%, the nickel content is 9.0% to 12.0%, and the titanium content is at most 0.70%.
[0172] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X6CrNiNb18-10 (material number: 1.4550), wherein the carbon content of the stainless steel is ≤ 0.08%, the chromium content is 17.0% to 19.0%, the nickel content is 9.0% to 12.0%, and the niobium content is at most 1.00%.
[0173] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X3CrNiCu18-9-4 (material number: 1.4567), wherein the carbon content of the stainless steel is ≤0.04%, the chromium content is 17.0% to 19.0%, the nickel content is 8.5% to 10.5%, and the copper content is 3.0% to 4.0%.
[0174] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X10CrNi18-8 (material number: 1.4310), wherein the carbon content of the stainless steel is 0.05% to 0.15%, the chromium content is 16.0% to 19.0%, the molybdenum content is ≤0.80%, and the nickel content is 6.0% to 9.5%.
[0175] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X5CrNiMo17-12-2 (material number: 1.4401), wherein the carbon mass content of the stainless steel is ≤0.07%, the chromium mass content is 16.5% to 18.5%, the molybdenum mass content is 2.00% to 2.50%, the nickel mass content is 10.0% to 13.0%, and the nitrogen mass content is ≤0.10%.
[0176] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X2CrNiMo17-12-2 (material number: 1.4404), wherein the carbon mass content of the stainless steel is ≤0.030%, the chromium mass content is 16.5% to 18.5%, the molybdenum mass content is 2.00% to 2.50%, the nickel mass content is 10.0% to 13.0%, and the nitrogen mass content is ≤0.10%.
[0177] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X6CrNiMoTi17-12-2 (material number: 1.4571), wherein the carbon mass content of the stainless steel is ≤0.08%, the chromium mass content is 16.5% to 18.5%, the molybdenum mass content is 2.00% to 2.50%, the nickel mass content is 10.5% to 13.5%, and the titanium mass content is at most 0.70%.
[0178] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X2CrNiMoN17-13-3 (material number: 1.4429), wherein the carbon mass content of the stainless steel is ≤0.030%, the chromium mass content is 16.5% to 18.5%, the molybdenum mass content is 2.5% to 3.0%, the nickel mass content is 11.0% to 14.0%, and the nitrogen mass content is 0.12% to 0.22%.
[0179] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X2CrNiMo18-14-3 (material number: 1.4435), wherein the carbon mass content of the stainless steel is ≤0.030%, the chromium mass content is 17.0% to 19.0%, the molybdenum mass content is 2.5% to 3.0%, the nickel mass content is 12.5% to 15.0%, and the nitrogen mass content is ≤0.10%.
[0180] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X3CrNiMo17-13-3 (material number: 1.4436), wherein the carbon mass content of the stainless steel is ≤0.05%, the chromium mass content is 16.5% to 18.5%, the molybdenum mass content is 2.5% to 3.0%, the nickel mass content is 10.5% to 13.0%, and the nitrogen mass content is ≤0.10%.
[0181] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X2CrNiMoN17-13-5 (material number: 1.4439), wherein the carbon mass content of the stainless steel is ≤0.030%, the chromium mass content is 16.5% to 18.5%, the molybdenum mass content is 4.0% to 5.0%, the nickel mass content is 12.5% to 14.5%, and the nitrogen mass content is 0.12% to 0.22%.
[0182] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X1NiCrMoCu25-20-5 (material number: 1.4539), wherein the carbon mass content of the stainless steel is ≤0.020%, the chromium mass content is 19.0% to 21.0%, the molybdenum mass content is 4.0% to 5.0%, the nickel mass content is 24.0% to 26.0%, the copper mass content is 1.20% to 2.00%, and the nitrogen mass content is ≤0.15%.
[0183] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X2CrNiMnMoNbN25-18-5-4 (material number: 1.4565), wherein the carbon mass content of the stainless steel is ≤0.030%, the chromium mass content is 24.0% to 26.0%, the molybdenum mass content is 4.0% to 5.0%, the nickel mass content is 16.0% to 19.0%, the manganese mass content is 5.0% to 7.0%, the nitrogen mass content is 0.30% to 0.60%, and the niobium mass content is ≤0.15%.
[0184] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X1NiCrMoCuN25-20-7 (material number: 1.4529), wherein the carbon mass content of the stainless steel is ≤0.020%, the chromium mass content is 19.0% to 21.0%, the molybdenum mass content is 6.0% to 7.0%, the nickel mass content is 24.0% to 26.0%, the copper mass content is 0.50% to 1.50%, and the nitrogen mass content is 0.15% to 0.25%.
[0185] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X1CrNiMoCuN20-18-7 (material number: 1.4547), wherein the carbon mass content of the stainless steel is ≤0.020%, the chromium mass content is 19.5% to 20.5%, the molybdenum mass content is 6.0% to 7.0%, the nickel mass content is 17.5% to 18.5%, the copper mass content is 0.50% to 1.00%, and the nitrogen mass content is 0.18% to 0.25%.
[0186] Alternatively, the stainless steel may be an austenitic corrosion-resistant stainless steel with the material abbreviation X1CrNiMoCuN24-22-8 (material number: 1.4652), wherein the carbon mass content of the stainless steel is ≤0.020%, the chromium mass content is 23.0% to 25.0%, the molybdenum mass content is 7.0% to 8.0%, the nickel mass content is 21.0% to 23.0%, the manganese mass content is 2.0% to 4.0%, and the nitrogen mass content is 0.45% to 0.55%.
[0187] In another embodiment of the present invention, the medical product is a medical device, preferably a surgical device. The device can also be a reusable device or a disposable device ("disposable device").
[0188] Furthermore, the device may be a minimally invasive device, ie a device that can be used in minimally invasive surgery.
[0189] The surgical instrument may in particular be selected from the group consisting of expansion instruments, clamping instruments, clamping instruments, cutting instruments, suturing devices, endoscopes and combined instruments.
[0190] For example, the dilation instrument can be a wound hook, a retractor, a wound dilator, a sternal dilator, a wound retractor, a scope, or a trocar cannula.
[0191] For example, the grasping instrument may be forceps, clamps, a needle holder or a grasping forceps.
[0192] For example, the clamping device may be a soft clip, particularly for temporary occlusion of the intestine and small vessels, or a preparatory clip.
[0193] For example, the cutting instrument can be a scalpel, a knife, scissors, branch forceps, bone splitters, ring forceps, electrocautery, turbinate knife, cautery, or ultrasonic scalpel.
[0194] The stapling device may in particular be a stapler (stapler) or a staple remover.
[0195] Combined instrument can be for example clamping and accurately cutting the interior staple or the staple of hollow organ simultaneously.In addition, combined instrument can be a combined needle holder, which can clamp and cut as a universal suturing device.
[0196] Additionally, the surgical instrument may be a hammer.
[0197] Furthermore, the surgical instrument can be a chisel, in particular a flat chisel or a hollow chisel, for example a bone hollow chisel, or a curette, in particular a bone curette.
[0198] Furthermore, the surgical instrument may be a probe.
[0199] Additionally, the surgical instrument may be a bone punch.
[0200] Furthermore, the surgical instrument may be a joystick or a lifter or a respirator.
[0201] In a second aspect, the present invention relates to a medical product comprising or consisting of a metal or an alloy, wherein the medical product is manufactured or manufacturable by the method according to the first aspect of the invention and / or has at least one of the following features:
[0202] - a pitting potential of 100 mV to 1200 mV, in particular 200 mV to 800 mV, preferably 400 mV to 500 mV (measured relative to a standard hydrogen electrode), and / or
[0203] - a contact angle of 80° to 140°, in particular 90° to 130°, preferably 100° to 120°, and / or
[0204] A passivation layer, in particular made of chromium oxide, having a thickness of 1 nm to 10 nm, in particular 3 nm to 10 nm, preferably 5 nm to 10 nm, which at least partially, in particular only partially or completely, coats the surface of the medical product.
[0205] The above pitting potential and contact angle are particularly advantageous in terms of the corrosion resistance of medical products.
[0206] In the context of the present invention, the expression "pitting potential" is understood to mean an electrochemical potential, which can be determined by an electrochemical cell using a three-electrode arrangement. The pitting potential is characterized by a rapid rise in current and describes the collapse of the passive layer as pitting occurs. An increase in the pitting potential improves corrosion resistance by reducing the tendency to pitting. The pitting potential can be measured according to ASTM G5-13-1 or DIN EN ISO 10993-15.
[0207] In the context of the present invention, the expression "contact angle" is understood to mean the angle that a liquid drop on the surface of a medical product forms with respect to its surface. A reduced contact angle is associated with a reduced contact of the liquid drop on the surface of the medical product. A reduction in the contact angle particularly advantageously results in an improvement in the corrosion resistance and cleanability of the medical product.
[0208] The contact angle can be measured according to ASTM D 7334-08. Alternatively, the contact angle can be measured by a contact angle measuring instrument (Contact Angle System OCA 15Plus) from dataPhysics and using a 0.9% sodium chloride solution (B. Braun), wherein the drop volume is 1 μl. For the contact angle measurement, the sample in this case can be cleaned in the conventional manufacturing process and cleaned in demineralized water in an ultrasonic bath for 5 minutes before the measurement, wherein the sample is cleaned with demineralized water and blown dry with oil-free compressed air just before the measurement.
[0209] The medical product is preferably a medical device, preferably a surgical device.
[0210] With regard to further features and advantages of the medical product, to avoid repetitions, reference is made entirely to the statements given in the context of the first aspect of the invention. The features and advantages described therein in relation to the method and the medical product also apply mutatis mutandis to the medical product according to the second aspect of the invention.
[0211] Other features and advantages of the present invention are derived from the description of the following preferred embodiments of the claims and reference examples. Here, the features of the present invention can be implemented individually or in combination with each other. The embodiments described below are used to further illustrate the present invention without limiting it thereto.
[0212] Examples
[0213] 1. Surface treatment of surgical instruments or representative samples thereof according to the method of the present invention
[0214] The specimens used were made of the same material (X20Cr13) and the same manufacturing steps as the surgical instruments (eg clips, needle holders, hard metal shears, etc.).
[0215] The devices were subjected to SEM / EDX analysis (foreign material and material overlap).
[0216] Potentiodynamic testing (pitting potential) was also performed on the device.
[0217] Contact angle measurements (Contact Angle) were performed on the sample sheets (flat surface without shadows).
[0218] The scratch resistance measurement (volume of wear scar) was performed by means of a pin-on-disc test on the sample pieces.
[0219] Prior to surface treatment, surgical instruments and sample sheets were formed and heat treated according to the current surgical instrument production chain.
[0220] For subsequent surface treatment, the surgical instruments (Aesculap clips BH110R) and the sample pieces were first brightened by slide grinding in an acidic solution for a period of four hours and then by slide grinding in an aqueous solution for a period of one hour.
[0221] Thereafter, the surgical instruments and the sample pieces were treated by blasting. The blasting agent used was stainless steel wire particles with an average ball diameter of 300 μm. An ejector blasting device was used for blasting. The blasting was carried out at a pressure of 2 bar.
[0222] Subsequently, the surfaces of the surgical instruments and the sample pieces were electrochemically treated at 80° C. in an electrolyte consisting of phosphoric acid (38% to 58% by weight) and sulfuric acid (26.6% to 52.0% by weight). To this end, the surfaces of the surgical instruments and the sample pieces were first electrochemically treated at 18.5 A / dm 2 The electropolishing was carried out for 90 seconds. A voltage of 5 to 6 volts was set here. Thereafter, the current density was 1.9 A / dm 2 The electrochemical etching was continued for 90 seconds. Here, a voltage of 1.8 to 2.1 V was set. Finally, the current density was again set at 18.5 A / dm 2 The electropolishing was performed for 10 seconds. A voltage of 5 to 6 V was set here.
[0223] Thereafter, the surfaces of the surgical instruments and the specimens were passivated. For this purpose, the surgical instruments and the specimens were immersed in 14.4% by weight nitric acid. The passivation was carried out at a temperature of 40° C. for a period of 10 minutes.
[0224] Finally, the device and sample sheet were dried at 80°C for 10 minutes in air atmosphere.
[0225] After the surface treatment of the surgical instrument and the test piece, no material overlap or material superposition and no foreign material transfer were found. The pitting potential of the instrument was 565 mV. The contact angle of the sample piece was 106.8°. Due to the small amount of wear, the volume of the wear scar could not be measured.
[0226] 2. Surface treatment of surgical instruments according to general types of methods
[0227] The surgical instrument (Aesculap clip BH110R) and the sample piece were first treated by slide grinding for a period of four hours. Thereafter, the surgical instrument and the sample piece were brightened for a period of one hour.
[0228] Thereafter, the surgical instrument and the specimen were treated by spraying. For this purpose, glass beads with an average diameter of 40 μm to 70 μm were used. The spraying was carried out in an ejector spraying device at a pressure of 4 bar.
[0229] The surgical instruments and the specimens were subsequently passivated. For this purpose, a 10% by weight citric acid solution was used. The passivation was carried out at a temperature of 55° C. for a period of 10 minutes.
[0230] After the surface treatment of the surgical instrument and the sample sheet, a lot of material overlap or material superposition was found. In addition, 1.2% of foreign material transfer could be detected. The pitting potential of the corrosion specimen was 356mV. In addition, the contact angle of the sample sheet was 66.0°. The volume removal in the wear scar was 55244μm 3 .
[0231] 3. Conclusion
[0232] The above comparison of the process of the invention and the process of the general type shows that the process of the invention produces a more corrosion-resistant, especially more scratch-resistant product. In addition, the process of the invention is suitable for reducing the risk of surface discoloration compared to the process of the general type. In addition, the process of the invention produces a product that can be cleaned better (see the measured contact angle).
Claims
1. A method for surface treatment and / or manufacturing of a medical product, wherein the medical product comprises or consists of a metal or an alloy, characterized in that The method comprises the following steps: a) Frosting the surface of medical products, b) Electropolishing of frosted surfaces of medical products, c) electrochemically etching the ground and electropolished surface of the medical product, and d) electropolishing the frosted, electropolished and electrochemically etched surface of the medical product, wherein step b) and step d) are each conducted at a voltage of 2.0 V to 10.0 V and / or at a flow rate of 5 A / dm 2 Up to 50A / dm 2 and step c) is carried out at a voltage of 1.2 V to 1.8 V and / or at a current density of 1.4 A / dm 2 Up to 2.4A / dm 2 The current density is carried out.
2. A medical product comprising or consisting of a metal or alloy, which is manufactured or manufacturable by the method according to claim 1 and comprises - A passivation layer having a thickness of 1 nm to 10 nm, which at least partially coats the surface of the medical product.